About detectability assessment of radar targets situated on underlying surface - Масловский, А. А.; Легенький, М. Н. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 1970)
In this paper methods for calculating scattering of electromagnetic field on the complex form object, that situated on the underlying surface were considered. The methodic for statistical processing of obtained data, that gives an ability to obtain the objects detection possibility dependence on a radar resolution was presented. The similarity of wave scattering on the complex form object, which situated on underlying surface and wave scattering on the corner reflector was shown. The possibility of object's reflection level reducing, with the help of sloping the object's sidewalls was introduced. With using the introduced methodic of statistical results processing is shown, that object with inclined sidewalls is less detectable, then source one.